Fear Avoidance Beliefs in College Athletes with a History of Ankle Sprain - Fukano, Mako; Mineta, Shinshiro; Hirose, Norikazu (International Journal of Sports Medicine, 2020)
Ankle sprains are the most prevalent injuries, and elevated fear avoidance beliefs after ankle sprain episodes could inhibit athletic performance and contribute to residual symptoms, such as functional and/or mechanical instability. However, it remains unclear how fear avoidance beliefs differ according to conditions of posttraumatic sequelae. The purpose of this study was to determine whether fear of movement/reinjury differed between individuals with and without functional ankle instability (FI, NFI) and healthy controls (CON) and to examine the relationship between fear and ankle joint laxity by sex. Participants (115 male athletes, 105 female athletes) completed the Identification of Functional Ankle Instability, Athlete Fear Avoidance Questionnaire (AFAQ), Tampa Scale for Kinesiophobia (TSK), and ankle joint laxity test. Total 168 athletes (79 males, 89 females) data were eligible for analysis. The results demonstrated that fear of movement/reinjury was lower in individuals in the absence of functional ankle instability although they experienced ankle sprain (FI; TSK=38.6±4.5, AFAQ=27.4±6.2, NFI; TSK=35.7±5.6, AFAQ=24.5±6.6). The fear of movement/reinjury had correlation with ankle joint laxity only in female athletes (TSK; r=0.285, p=0.013, AFAQ; r 0=0.322, p=0.045).
Keywords: fear of movement/reinjury; ankle sprain; joint laxity; sex-based differences